Índices de diversidade da entomofauna em cultivo de milho - Total diversity index and that of parasitic, and predators in the third phase of growing corn plantas Zea mays L., were determined in Pacajus, Ceará, Brazil. (Revista Ciência Agronômica, 2023)
RCA